Modelling and computational improvements to the simulation of single vector-boson plus jet processes for the ATLAS experiment - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (Journal of high energy physics)
This paper presents updated Monte Carlo configurations used to model the production of single electroweak vector bosons (W, Z/gamma*) in association with jets in proton-proton collisions for the ATLAS experiment at the Large Hadron Collider. Improvements pertaining to the electroweak input scheme, parton-shower splitting kernels and scale-setting scheme are shown for multi-jet merged configurations accurate to next-to-leading order in the strong and electroweak couplings. The computational resources required for these set-ups are assessed, and approximations are introduced resulting in a factor three reduction of the per-event CPU time without affecting the physics modelling performance. Continuous statistical enhancement techniques are introduced by ATLAS in order to populate low cross-section regions of phase space and are shown to match or exceed the generated effective luminosity. This, together with the lower per-event CPU time, results in a 50% reduction in the required computing resources compared to a legacy set-up previously used by the ATLAS collaboration. The set-ups described in this paper will be used for future ATLAS analyses and lay the foundation for the next generation of Monte Carlo predictions for single vector-boson plus jets production.